Market entry strategies for born digitals - Nousiainen, Totte; Siukkola, Venla (My University, 2026)
Tämä kandidaatin tutkielma tarkastelee born digital -yrityksiä sekä kyseisille yrityksille soveltuvia markkinoillemenotapoja (entry modes). Born digital -yritykset ovat digitalisaation tuoma yritysmuoto, jossa yrityksen perustaminen on tapahtunut digitaalisilla alustoilla. Yleistä näille on nopea kansainvälistyminen, joka tuo markkinoillemenotavan arvioinnin keskeiseksi osaksi liiketoiminnan käynnistämistä ja strategian kehittämistä.

This bachelor's thesis examines born digital companies and entry modes suitable for them. Born digital companies are a company with a purely digital product offering, made possible through digitalization. Rapid internalization upon establishment is a common characteristic for born digitals, and this establishes entry mode choices as a central part of starting the company and their strategy management.
Keywords: digital competence; foreign trade; strategic planning; fi=Kansainvälinen liiketoiminta|en=International Business|; fi=Kansainvälisen liiketoiminnan kandidaattiohjelma|en=Bachelor Programme in International Business|